Website Development as an Institutional Innovation for Implementing Village Product Bank and Green Accounting Integration Model - Oktaviani, Siska Aprilia; Pinandita, Candra Pramula; Yudhistira, Prillinaya; WIjaya, Dwi Indriani Fidiastutik; Nugraheni, Ponti Primastuti Aulia; Fitrianto, Dwi Wahid; Yulianto, Alfin Dwi; Anwar, Imam Saiful (Worksheet : Jurnal Akuntansi, 2025)
The integration of village product banks with green accounting provides institutional innovation to address the economic empowerment of MSMEs and environmental sustainability in rural communities. However, its implementation requires practical and easily accessible media to facilitate product marketing, management, and stakeholder transparency. This study aims to develop a website-based platform as a digital infrastructure to implement the integrated model of village product banks and green accounting. This study uses a research and development (R&D) approach, including needs analysis, concept design, and website development through collaboration with third parties. The novelty of the study lies in the combination of institutional innovation with digital transformation, enabling the operationalization of green accounting indicators in a web-based environment to support the marketing of village MSME products. The urgency of the research is supported by the increasing need for digital platforms to support the marketing of local products and sustainable development practices in rural areas. The resulting platform is a website www.bankprodukkarangpring.com as a means of marketing MSME products in Karangpring village with green accounting integration to increase transparency, environmental accountability, and the competitiveness of local products.